2003
DOI: 10.1590/s0102-05362003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Teor de cálcio em frutos de diferentes cultivares de feijão-vagem

Abstract: Foi determinada a concentração de cálcio em frutos de feijão-vagem cultivares: Xera, Paulista, Florence, 274, F-15, Nerina, Anseme e UEL-1, em dois experimentos, em 1997 e 1998 em Londrina. O delineamento experimental foi de blocos ao acaso com quatro repetições. Foram avaliadas as vagens classificadas como número 4 (8,3 a 9,4 mm de diâmetro). As concentrações de cálcio das cultivares foram comparadas pelo teste de Duncan a P < 0,05. Nos dois anos analisados, a cultivar Xera apresentou as maiores concentraç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Feltrin Macarrão Napoli beans contained more calcium than the other genotypes, while Isla Manteiga Baixo had the highest magnesium content, differing from UEL 1 (Table 3). Differences in the concentration of calcium in snap beans is attributed to genetic variation, as well as its availability in the soil, as reported by Miglioranza, Araujo, Endo, Souza and Montanari (2003) in snap bean cultivars of bush growth. Additional studies have reported that calcium is related to the physiological quality of seeds (Bevilaqua, Silva, & Possenti, 2002).…”
Section: Resultsmentioning
confidence: 65%
“…Feltrin Macarrão Napoli beans contained more calcium than the other genotypes, while Isla Manteiga Baixo had the highest magnesium content, differing from UEL 1 (Table 3). Differences in the concentration of calcium in snap beans is attributed to genetic variation, as well as its availability in the soil, as reported by Miglioranza, Araujo, Endo, Souza and Montanari (2003) in snap bean cultivars of bush growth. Additional studies have reported that calcium is related to the physiological quality of seeds (Bevilaqua, Silva, & Possenti, 2002).…”
Section: Resultsmentioning
confidence: 65%
“…However, the 540 mg 100 g -1 dry matter calcium content in the pods was attained with the addition of Ca 600 mg L -1 in the nutrient solution, whereas in this study a close concentration (520 mg 100 g -1 ) was observed with the application of 300 mg L -1 . Differences in the pod calcium concentration among cultivars of snap bean were ascertained to genotype efficiency in Ca absorption (Quintana et al, 1996) and shown to be related to pod transpiration rate, stomata number and stomata size (Miglioranza et al, 2003).…”
Section: Calcium Distribution In the Snap Bean Plantmentioning
confidence: 99%
“…P. vulgaris contents micronutrients, such as phosphorus (P) and calcium (Ca) are essential minerals for both human diet and provide vital functions in plants and are required in large quantities (White and Broadley 2009). Among minerals, calcium stands out due to its importance in bone and tooth formation, as well as its role in growth and its being a co-factor/regulator in various biochemical reactions (Miglioranza et al 2003). Further, beans are an excellent dietary alternative to dairy products since they contain a high quantity of calcium (Frossard et al 2000).…”
Section: Introductionmentioning
confidence: 99%